Release of endothelial cell associated VEGFR2 during TGF-β modulated angiogenesis in vitro. Issue 1 (December 2017) - Jarad, M.; Kuczynski, E.; Morrison, J.; Viloria-Petit, A.; Coomber, B.
Abstract Background Sprouting angiogenesis requires vascular endothelial proliferation, migration and morphogenesis. The process is regulated by soluble factors, principally vascular endothelial growth factor (VEGF), and via bidirectional signaling through the Jagged/Notch system, leading to assignment of tip cell and stalk cell identity. The cytokine transforming growth factor beta (TGF-β) can either stimulate or inhibit angiogenesis via its differential surface receptor signaling. Here we evaluate changes in expression of angiogenic signaling receptors when bovine aortic endothelial cells were exposed to TGF-β1 under low serum conditions. Results TGF-β1 induced a dose dependent inhibition of tip cell assignment and subsequent angiogenesis on Matrigel, maximal at 5.0 ng/ml. This occurred via ALK5-dependent pathways and was accompanied by significant upregulation of the TGF-β co-receptor endoglin, and SMAD2 phosphorylation, but no alteration in Smad1/5 activation. TGF-β1 also induced ALK5-dependent downregulation of Notch1 but not of its ligand delta-like ligand 4. Cell associated VEGFR2 (but not VEGFR1) was significantly downregulated and accompanied by reciprocal upregulation of VEGFR2 in conditioned medium. Quantitative polymerase chain reaction analysis revealed that this soluble VEGFR2 was not generated by a selective shift in mRNA isoform transcription. This VEGFR2 in conditioned medium was full-length protein and was associated with increased soluble HSP-90, consistent with a possible shedding of microvesicles/exosomes. Conclusions Taken together, our results suggest that endothelial cells exposed to TGF-β1 lose both tip and stalk cell identity, possibly mediated by loss of VEGFR2 signaling. The role of these events in physiological and pathological angiogenesis requires further investigation.